Quality development of local weaving fabrics among women in Ban Na Duang local weaving group, Loei Province - Phon-ngam, Patthira; Trongthieng, Wattana (Srinakharinwirot Research and Development Journal of Humanities and Social Sciences, 2025)
The purposes of this research were 1) to study the problems and needs in the quality development of indigenous weaving fabrics, in the group of local weaving women at Ban Na Duang Na Duang District, Loei Province and 2) to improve the quality of indigenous weaving fabrics in the group of local weaving women at Ban Na Duang. It is a participatory action research using in-depth interviews, focus group discussions and brainstorming sessions. The results found that 1) problems in developing the quality of local woven fabrics the group produces Mudmee cloth using wisdom passed down from ancestors. There is a problem with designing cloth patterns that lack the identity of the group and community. There are no modern patterns due to lack of knowledge in new and modern production processes, the group would like to have training in designing fabric patterns. In the community, they wanted a pattern that was unique to the community, namely the bat pattern group, want to dye natural dyes and 2) to develop the quality of local woven fabrics, training in fabric pattern design has been conducted. Production process natural dyeing and marketing strategy Including study visits. As a result, the group was able to produce woven fabric with a pattern that was the identity of the group. Can be produced according to community product standards and applied for a design patent. As for the marketing strategy, there is product promotion in various forms such as brochures, flyers, advertising, and the development of distribution channels such as retail stores, community stores, and ready-made garment shops. Supporting the display of woven fabric products at various events at the local and provincial levels, including adding value to products by processing a variety of products, such as bags, satchels, TV covers, refrigerators, shirts.